Insights into the catalytic activity of Ru/NaY catalysts for efficient H-2 production through aqueous phase reforming - Gogoi, Pranjal; Nagpure, Atul S.; Kandasamy, Prabu; Satyanarayana, C. V. V.; Raja, Thirumalaiswamy (Sustainable Energy & Fuels, 2020)
Ruthenium nanoparticles supported on NaY zeolite catalysts were synthesized by a simple ion exchange method. The structural and morphological features of the catalysts were systematically investigated using numerous techniques such as N-2-sorption, XRD, CO2-TPD, H-2-TPR, TEM, SEM, ICP-OES, TGA, CHN analysis, XPS, in situ CO-FTIR and NMR spectroscopy. These novel Ru-NaY catalysts were highly active and selective for H-2 production through aqueous phase reforming (APR) of glycerol and ethylene glycol. Among the various catalysts evaluated for H-2 production, the 3 wt% Ru-NaY catalyst demonstrated the highest catalytic performance with excellent H-2 selectivity and this catalyst exhibits better activity as compared to many state of the art catalysts reported so far. The superior catalytic activity of 3 wt% Ru-NaY was attributed to the appropriate Ru metal loading, good metal dispersion, small size of Ru nanoparticles, better metal-support interaction, and higher availability of catalytically active sites (Ru-0) and facilitated water gas shift (WGS) reaction. This catalytic activity result clearly shows that NaY zeolite supported Ru nanoparticles catalysts have excellent potential for H-2 production from biomass-derived compounds.

Investigation of structural and morphological insights of nanostructured layered double hydroxides: catalytic activity in aldol condensation - Bhagat, Shailesh K.; Nagpure, Atul S.; Lanjewar, Mamata R.; Gode, Nilesh G.; Thakare, Sanjay R. (Journal of Porous Materials, 2024)
Layered double hydroxides (LDHs) materials finds extensive applications in numerous fields such as medical science, industrial sector, agriculture and food, catalysis, polymers, nanotechnology, etc. The LDHs properties (structural, textural, morphological, spectroscopic and theoretical insights) can be design for achieving required materials for particular application in scientific areas. In the current investigation, we have synthesized mesoporous nanostructured LDHs materials via microwave, sonication and stirring method. The nanostructured LDHs was scientifically characterized by various physico-chemical techniques like XRD, N2 sorption, TGA, solid state one-dimensional 27Al magic angle spinning NMR spectroscopy, XPS, Raman Spectroscopy, FT-IR, ICP-OES, Electron Microscopy (SEM, FE-SEM, TEM and HR-TEM), EDX, elemental analysis, etc. On the basis of experimental study, it can be evidently witnessed that nanostructured LDHs materials was formed with good crystalline mesoporous nature. Solid state 27Al NMR showed single and sharp 27Al NMR signal at chemical shift value of + 1.4 ppm, strongly suggesting the presence of octahedral (Oh) AlO6 coordination site in all as-synthesized LDHs. Microwave and sonication techniques furnishes regularly dispersed well-developed flower-shaped nanocrystals however, stirring method gives mostly agglomerated nano-sized platelets. The mechanistic insights for the fabrication of nanostructures LDHs via microwave, sonication and stirring process were also highlighted. The different LDHs materials were utilized in the aldol condensation reaction of furfural with acetone for understanding structure-activity correlation. Microwave and sonication methodologies can be further exploited for the synthesis of many other inorganic-organic nanocomposites materials with stable and good dispersion of nanocrystals in addition to desired morphology and catalytic activity.
Keywords: Aldol condensation; catalysis; Flower-shaped nanocrystals; layered double hydroxides; Microwave and sonication techniques; Nanostructured materials